2016
DOI: 10.1177/1359105315592046
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ experiences and perceived (dis)advantages of the three main outlet types for alcohol purchases

Abstract: Based on the existing literature, relevant determinants of availability for on-premises locations, off-premises locations, and the Internet were qualitatively explored and categorized by "experts" consisting of underage alcohol purchasers. In total, 14 focus group discussions were conducted with 94 Dutch adolescents. For on-premises locations, the high prices were perceived as the biggest disadvantage, and the ease to circumvent legal age limits as the biggest advantage. For off-premises locations, the cheap p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Store location was an important factor for adolescents and young adults in Australia when choosing where to buy alcohol [ 35 ]. According to teenagers in a study in the Netherlands [ 36 ], proximity to off‐premise outlets provided an opportunity for spontaneous purchase of alcohol. The easy access to alcohol among university students on a campus in Denmark was also mentioned as participants could buy alcohol in the canteen and from vending machines [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Store location was an important factor for adolescents and young adults in Australia when choosing where to buy alcohol [ 35 ]. According to teenagers in a study in the Netherlands [ 36 ], proximity to off‐premise outlets provided an opportunity for spontaneous purchase of alcohol. The easy access to alcohol among university students on a campus in Denmark was also mentioned as participants could buy alcohol in the canteen and from vending machines [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…Facilitators for alcohol purchases, such as convenience, price and lack of ID checks, appeared relevant to both mixed‐retail and alcohol‐only shops. One study compared participants' preferences and found that adolescents in the Netherlands chose grocery stores over alcohol‐only shops, because of perceived lower prices of alcohol products [ 36 ]. However, mixed‐retailers might increase alcohol exposure to vulnerable groups who use the shop for other purchases.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations